2021
DOI: 10.1002/jmv.27026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of saliva with oral and nasopharyngeal swabs for SARS‐CoV‐2 detection on various commercial and laboratory‐developed assays

Abstract: The accurate laboratory detection of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a crucial element in the fight against coronavirus disease 2019 (COVID-19). Reverse transcription-polymerase chain reaction testing on combined oral and nasopharyngeal swab (ONPS) suffers from several limitations, including the need for qualified personnel, the discomfort caused by invasive nasopharyngeal sample collection, and the possibility of swab and transport media shortage. Testing on saliva would re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 17 publications
2
17
0
1
Order By: Relevance
“…Commercial assays are: Simplexa™ COVID‐19 Direct Kit (DiaSorin Molecular LLC), cobas® SARS‐CoV‐2 performed with the cobas®6800/8800 systems (Roche), and Allplex™ 2019‐nCoV assay with thermal lysis (Seegene). Laboratory developed tests (LDTs) targeting the structural protein envelope E gene were performed on LightCycler® 480 II Instrument (Roche) and CFX96 Touch Real‐Time PCR System (BioRad) after thermal lysis or RNA extraction using NucliSens easyMAG (bioMérieux) as previously described 4,6 . Samples were considered positive if they met the interpretation criteria of the manufacturer or if C t values were ≤40 for LDTs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Commercial assays are: Simplexa™ COVID‐19 Direct Kit (DiaSorin Molecular LLC), cobas® SARS‐CoV‐2 performed with the cobas®6800/8800 systems (Roche), and Allplex™ 2019‐nCoV assay with thermal lysis (Seegene). Laboratory developed tests (LDTs) targeting the structural protein envelope E gene were performed on LightCycler® 480 II Instrument (Roche) and CFX96 Touch Real‐Time PCR System (BioRad) after thermal lysis or RNA extraction using NucliSens easyMAG (bioMérieux) as previously described 4,6 . Samples were considered positive if they met the interpretation criteria of the manufacturer or if C t values were ≤40 for LDTs.…”
Section: Methodsmentioning
confidence: 99%
“…NucliSens easyMAG (bioMérieux) as previously described. 4,6 Samples were considered positive if they met the interpretation criteria of the manufacturer or if C t values were ≤40 for LDTs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less invasive and self‐collected specimens, such as saliva or gargle, have been proposed for COVID‐19 diagnostic purposes. Systematic reviews on the sensitivity of SARS‐CoV‐2 testing using saliva revealed a good sensitivity as well as important drawbacks limiting its use, such as specimen viscosity and the inability of some individuals to produce sufficient quantity for testing 4–6 . There have been less publications using gargle as an alternative specimen for SARS‐CoV‐2 diagnostic 7–12 .…”
Section: Introductionmentioning
confidence: 99%
“…The collection of this sample, although is not painful, is very unpleasant and irritating for the patient and represents a risk for the spread of the virus as respiratory secretions are the main route of infection. 8 Therefore, to avoid patient discomfort as well as a duplicate exposure of the healthcare personnel, the objective of this study has been to study the possibility of using a single nasopharyngeal swab to perform both the Ag test and RT-PCR analysis when it is considered necessary. 1).…”
Section: Introductionmentioning
confidence: 99%